Legal systems of the world : a political, social, and cultural encyclopedia Vol. 2 : E-L - Kritzer, Herbert M., 1947- (Pentagon Press, 2008)
"Written by an international team of more than 350 legal scholars, the more than 400 signed entries cover legal systems of countries from around the world, Australia, and the provinces of Canada; transnational systems (International Court of Justice); general systems (Islamlic law, indigenous, and folk legal systems); and key concepts. Each country profile includes a map with an inset of its location on the globe, general information about the country, its history, diagrams of its court structure, the evolution of its legal framework, its current structure, staffing or how judges are appointed, any specialized judicial bodies (i.e. military court), and the impact that the legal system has had on the country. Articles conclude with references and a bibliography. Academic and public libraries will find this source invaluable for comparative studies in legal and judicial systems."--"The Best of the Best Reference Sources," American Libraries, May 2003.